2022
DOI: 10.1021/acs.macromol.1c02083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Poly(N-Isopropylacrylamide) Microgel Aqueous Suspension Investigated by Dielectric Relaxation Spectroscopy

Abstract: Free-radical precipitation polymerization was used to make non-ionic poly(N-isopropylacrylamide) (PNIPAM) microgel particles. On the synthesized PNIPAM microgel particles, a dynamic light scattering experiment was performed, and hydrodynamic radii were determined to be roughly 240 and 125 nm for temperatures of 298 and 313 K, respectively. Dielectric experiments were carried out on a 10 wt % PNIPAM microgel aqueous suspension at temperatures extending from 288 to 323 K, including volume phase transition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In addition, experiments and MD simulations indicate that there is also dehydration of the hydrophobic moieties, which leads to a favorable entropy gain. ,,, However, it is clear that water is critical to the underlying transition mechanism and plays a crucial role in thermo-responsive polymers and, more generally, hydrogel materials. The limited studies on the water structure and dynamics using techniques such as dielectric relaxation, , NMR, and quasi-elastic neutron scattering , show a reduction in bound or hydrating water near the polymer through the LCST, which exhibits much slower dynamics than bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, experiments and MD simulations indicate that there is also dehydration of the hydrophobic moieties, which leads to a favorable entropy gain. ,,, However, it is clear that water is critical to the underlying transition mechanism and plays a crucial role in thermo-responsive polymers and, more generally, hydrogel materials. The limited studies on the water structure and dynamics using techniques such as dielectric relaxation, , NMR, and quasi-elastic neutron scattering , show a reduction in bound or hydrating water near the polymer through the LCST, which exhibits much slower dynamics than bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the previously observed asymmetric relaxation processes in the MHz region of PNiPAM in aqueous systems comprise two individual processes, although the side-group rotational motion cannot be discerned when water is the solvent. Several studies used dielectric relaxation spectroscopy to study aqueous PNiPAM solutions and PNiPAM microgel aqueous suspensions in the vicinity of LCST. Water processes near the GHz region were analyzed and used to interpret the PNiPAM–water interactions as well as molecular structures of the system. Using the low-polarity solvent 1,4-dioxane in this study, we revealed that the PNiPAM has two individual relaxation modes in the MHz region.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports on the dielectric relaxation spectroscopy analysis of PNiPAM. In most cases, water has been considered the solvent, and the concentration or temperature dependency has been measured precisely. These reports have examined influences of the cross-linking density of PNiPAM microgel, charge effects on the chain, Maxwell–Wagner relaxation, and DC conductivity. Although dielectric spectra reflect the relaxation of both water and PNiPAM, the weaker relaxation signal from PNiPAM is hidden by the much stronger ones from water, DC conductivity, and electrode polarization, making it difficult to further analyze the PNiPAM chain dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on the idea of two kinds of water models, the contributions of each of the two kinds of water, both free water outside the microgel and confined water within the microgel, to the high-frequency relaxation spectrum were evaluated. Despite the extensive research on PNIPAM, [48][49][50][51][52][53][54][55] low temperature investigations of PNIPAM dispersions remain mostly unexplored. In this study, we used BDS to investigate the dielectric relaxation of ice of a frozen 10 wt% PNIPAM microgel aqueous suspension and compared it to other frozen polymer-water mixtures such as BSA, gelatin, and PVP of the same concentration in order to understand the mechanism of the temperature dependent dielectric relaxation behavior of ice in such partially crystallized polymer-water mixtures.…”
Section: Introductionmentioning
confidence: 99%